Dekonstruksi Seni Lukis Tradisional Jelekong sebagai Ekspresi Visual - Shopia Himatul Alya; Ariesa Pandanwangi; Ismet Zainal Effendi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Jelekong has a productive community of artists who produce commercial and mass paintings. This creation aims to create novelty in Jelekong painting by borrowing Jacques Derrida s Deconstruction to present alternative meanings. The creation method used is Alma M. Hawkins creation method which includes the stages of 1) exploration, 2) improvisation, and 3) implementation. The results of the creation of this work are two works entitled "To Bloom" and "To Flow" which show aspects of deconstruction that occur in the creative process which can also be identified in the ideas and visual aspects of the work. Metallic visualization is used as a marker of the transformation resulting from efforts to deconstruct the traditional Jelekong painting.